2009
DOI: 10.1139/f09-089
|View full text |Cite
|
Sign up to set email alerts
|

Geographic, anthropogenic, and habitat influences on Great Lakes coastal wetland fish assemblages

Abstract: We analyzed data from coastal wetlands across the Laurentian Great Lakes to identify fish assemblage patterns and relationships to habitat, watershed condition, and regional setting. Nonmetric multidimensional scaling (NMDS) ordination of electrofishing catch-per-effort data revealed an overriding geographic and anthropogenic stressor gradient that appeared to structure fish composition via impacts on water clarity and vegetation structure. Wetlands in Lakes Erie and Michigan with agricultural watersheds, turb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 57 publications
3
39
0
Order By: Relevance
“…This evidence implies that a change in fish community should be a synergistic consequence of the effect of changes in water quality, and the effect of water quality on plants and the subsequent impact on fish. While recent studies have shown the importance of both water quality (described in terms of water clarity) and aquatic vegetation assemblages to the Great Lakes fish community (Trebitz et al, 2009), no studies to our knowledge have directly investigated which of these two factors, water quality or macrophyte community, has a more prominent influence on fish composition. Ultimately, such investigations could refocus research efforts to improve wetland sampling and monitoring programs and provide enhancement of wetland restoration projects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence implies that a change in fish community should be a synergistic consequence of the effect of changes in water quality, and the effect of water quality on plants and the subsequent impact on fish. While recent studies have shown the importance of both water quality (described in terms of water clarity) and aquatic vegetation assemblages to the Great Lakes fish community (Trebitz et al, 2009), no studies to our knowledge have directly investigated which of these two factors, water quality or macrophyte community, has a more prominent influence on fish composition. Ultimately, such investigations could refocus research efforts to improve wetland sampling and monitoring programs and provide enhancement of wetland restoration projects.…”
Section: Introductionmentioning
confidence: 99%
“…(Janecek, 1990;Randall et al, 1996). Given that empirical studies evaluating the co-occurrence of fish and macrophyte taxa are scarce (see Janecek, 1990;McNair, 2006), there is a demand for papers that advance this branch of fish habitat research in order to gain a more detailed understanding of the complex connections between macrophyte and fish communities (Randall et al, 1996;Brazner and Beals, 1997;Trebitz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The geological history of drowned river-mouth lakes dates back ~10,000 years when the last glaciers retreated to the north and the rising Great Lakes water levels flooded the eroded river mouths. Their complex hydrodynamics can influence material transport and processing, with associated implications for biological structure and function (Trebitz et al, 2009;Larson et al, 2013). For example, fish composition within coastal wetlands differs depending on their Great Lake connectivity (i.e., lacustrine-protected vs barrier-beach lagoons, Trebitz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Their complex hydrodynamics can influence material transport and processing, with associated implications for biological structure and function (Trebitz et al, 2009;Larson et al, 2013). For example, fish composition within coastal wetlands differs depending on their Great Lake connectivity (i.e., lacustrine-protected vs barrier-beach lagoons, Trebitz et al, 2009). Due to their locations near areas of development and human population centers, many of these drowned river-mouth lakes are heavily utilized by humans, which can result in ecological impairment and loss of ecosystem services (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have focused on specific habitat components, such as aquatic macrophytes (Radomski and Goeman 2001), nearshore cover (Christensen et al 1996), substrate (Jennings et al 1999), and fish (Hook et al 2001), and variations in assessment methodologies and scale present uncertainty in integrating these to characterize ecosystem response. Although these studies generally indicate that shoreline protection projects can cause changes in the nearshore environment, including the lake bottom, the water column, and the biota (Brazner and Magnuson 1994;Goforth and Carman 2005;Trebitz et al 2009), the challenge is to understand the potential magnitude and the complexity of interactions among these factors.…”
Section: Introductionmentioning
confidence: 99%